Pengaruh Tablet Fe dan Kombinasi Tablet Fe dengan Yoga Pada Remaja Putri yang Mengalami Anemia dengan Dismenore - Aisya Astri Yunas; Hanom Husni Syam; Vita M.T.; Ruswana Anwar; Meita Dhamayanti; Ronny Lesmana (Jurnal Ners, 2025)
Dysmenorrhea and anemia are common health problems among adolescent girls, while pharmacological therapy has limitations, highlighting the need for safe and comprehensive alternative interventions. This study aimed to analyze the effects of Fe supplementation and the combination of Fe supplementation with yoga on hemoglobin levels and dysmenorrhea intensity in adolescent girls. A quasi-experimental design with a two-group pre-test post-test approach was employed. Participants were adolescent girls from SMAN 03 Rejang Lebong who received either Fe supplementation or a combination of Fe supplementation and yoga for four weeks. Data were analyzed using the Wilcoxon and Mann-Whitney tests. The results showed that the combination of Fe supplementation and yoga significantly improved hemoglobin levels and reduced dysmenorrhea intensity (p = 0.000). Moreover, the combination was more effective than Fe supplementation alone. These findings suggest that combining yoga with Fe supplementation can serve as an effective non-pharmacological strategy to manage anemia and dysmenorrhea among adolescent girls. Keywords: dysmenorrhea, anemia, Fe supplementation, yoga, adolescent girls